Non-covalent interaction of soy protein isolate and catechin: Mechanism and effects on protein conformation. (1st August 2022) - Dai, Shicheng; Lian, Ziteng; Qi, Weijie; Chen, Yashuang; Tong, Xiaohong; Tian, Tian; Lyu, Bo; Wang, Mengmeng; Wang, Huan; Jiang, Lianzhou
Graphical abstract: Highlights: The non-covalent interaction mechanism between SPI and catechin was studied. The quenching of SPI by catechin was mainly static quenching. The effect of catechin with different concentrations on SPI conformation was studied. Hydrophobic interactions and hydrogen bonds were main forces of SPI-Catechin complex. Abstract: Understanding the molecular mechanism behind protein–polyphenol interactions is critical for the application of protein–polyphenol compounds in foods. The purpose of this research was to investigate the non-covalent interaction mechanism between soy protein isolate (SPI) and catechin and its effect on protein conformation. We observed that particle size, ζ-potential, and polyphenol bound equivalents of SPI increased significantly after non-covalent modification with catechin. These changes caused SPI to aggregate and form a network-like structure. Fourier transform infrared spectroscopy (FTIR) indicated that increased catechin concentrations caused SPI to become looser and more disordered as its α-helix and β-sheet transformed into β-turn and random coil. Furthermore, internal structure of SPI was opened and its hydrophobic groups were exposed to a polar environment, which was demonstrated by decreased surface hydrophobicity. Thermodynamic analysis and molecular docking results showed that the main forces present between SPI and catechin were hydrophobic interactions and hydrogen bonds.